2021
DOI: 10.1371/journal.ppat.1009901
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid neddylation targets IRF7 and promotes host innate immunity against RNA viruses

Abstract: Neddylation, an important type of post-translational modification, has been implicated in innate and adapted immunity. But the role of neddylation in innate immune response against RNA viruses remains elusive. Here we report that neddylation promotes RNA virus-induced type I IFN production, especially IFN-α. More importantly, myeloid deficiency of UBA3 or NEDD8 renders mice less resistant to RNA virus infection. Neddylation is essential for RNA virus-triggered activation of Ifna gene promoters. Further explora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 58 publications
(87 reference statements)
0
19
0
Order By: Relevance
“…They also claimed that neddylation inhibition increases zebrafish sensitivity to SVCV infection. And tests about SeV infection showed similar results, demonstrating that during infection, NEDD8 directly targets the C-terminal lysine residues of IRF7 ( Figure 3 ) and partially improves its transcription by inhibiting its dimerization with the IFN-α repressor, IRF5 ( Zhao et al, 2021 ). Through neddylation, induction of type I IFN by RNA virus is promoted, especially that of IFN-α.…”
Section: Neddylation and Anti-viral Pathwaysmentioning
confidence: 73%
See 2 more Smart Citations
“…They also claimed that neddylation inhibition increases zebrafish sensitivity to SVCV infection. And tests about SeV infection showed similar results, demonstrating that during infection, NEDD8 directly targets the C-terminal lysine residues of IRF7 ( Figure 3 ) and partially improves its transcription by inhibiting its dimerization with the IFN-α repressor, IRF5 ( Zhao et al, 2021 ). Through neddylation, induction of type I IFN by RNA virus is promoted, especially that of IFN-α.…”
Section: Neddylation and Anti-viral Pathwaysmentioning
confidence: 73%
“…Zhao et al used mouse models with myeloid deficiency in UBA3 or NEDD8 to study the effects of neddylation on the response against RNA virus, and they found UBA3 absence results in impaired IFN-β (interferon-β) as well as IFN-α production in myeloid dendritic cells (mDCs), proposing that myeloid neddylation is required to induce IFN production upon Sendai virus (SeV) infection ( Zhao et al, 2021 ). Previous studies on zebrafish demonstrated that both interferon regulatory factor 3 (IRF3) and IRF7 are potential substrates of neddylation during spring viremia of carp virus (SVCV) infection and can activate anti-viral responses ( Yu et al, 2019 ).…”
Section: Neddylation and Anti-viral Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The PR-UBA3 interaction has notable implications for impacting antiviral immunity, based on strong evidence for a necessity of NEDDylation-associated cullin-RING E3 ubiquitin ligases in retroviral infections, as a means to overcome cellular viral restriction factors APOBEC and SAMHD1 (94). However, given the broad antiviral effect of NEDDylation inhibitor MLN4924 (95), and the role of NEDDylation in activating NF-kB, IRFs, and interferon production (96,97), it remains unclear how PR involvement in NEDDylation may impact ERVK activity.…”
Section: Ervk Protease Is Associated With the Apex Of Ubiquitin-like ...mentioning
confidence: 99%
“…5c). UBE2F is involved in neddylation, a posttranslational modification required for the nuclear translocation of IRF7 by myeloid cells following infection with RNA viruses and, thus, for the induction of type I IFN responses 47 . Collectively, these results document the molecular and cellular mechanisms through which archaic introgression has altered immune functions.…”
Section: Introductionmentioning
confidence: 99%